Diabetic Uterine Environment Leads to Disorders in Metabolism of Offspring - Dong, Ming-Zhe; Li, Qian-Nan; Fan, Li-Hua; Li, Li; Shen, Wei; Wang, Zhen-Bo; Sun, Qing-Yuan (Frontiers in Cell and Developmental Biology, 2021)
Aims: Research evidence indicates that epigenetic modifications of gametes in obese or di-abetic parents may contribute to metabolic disorders in offspring. In the present study, we sought to address the effect of diabetic uterine environment on the offspring metabolism. Methods: Type 2 diabetes mouse model was induced by high-fat diet combined with strep-tozotocin (STZ) administration. We maintained other effect factors constant and changed uterine environment by zygote transfers, and then determined and compared the offspring numbers, symptoms, body weight trajectories, and metabolism indices from different groups. Result: We found that maternal type 2 diabetes mice had lower fertility and a higher dystocia rate, accompanying the increased risk of offspring malformations and death. Compared to only a pre-gestational exposure to hyperglycemia, exposure to hyperglycemia both pre- and during pregnancy resulted in offspring growth restriction and impaired metabolism in adulthood. But there was no significant difference between a pre-gestational exposure group and a no exposure group. The deleterious effects, no matter bodyweight or glucose tolerance, could be rescued by transferring the embryos from diabetic mothers into normal uterine en-vironment. Conclusion: Our data demonstrate that uterine environment of maternal diabetes makes critical impact on the offspring health.